A Clock in the Sun?. Issue Volume 15:Issue S354(2019) (June 2019) - Russell, C. T.; Luhmann, J. G.; Jian, L. K.
Abstract: The sunspot cycle is quite variable in duration and amplitude, yet in the long term, it seems to return to solar minimum on schedule, as if guided by a clock with an average period of close to 11.05 years for the sunspot number cycle and 22.1 years for the magnetic cycle. This paper provides a brief review of the sunspot number cycle since 1750, discusses some of the processes controlling the solar dynamo, and provides clues that may add to our understanding of what controls the cadence of the solar clock.